Design of new M@ZnO nanocolloids: synthesis and shaping. (16th June 2008) - Grasset, F.; Cordier, S.; Molard, Y.; Perrin, C.; Nazabal, V.; Guilloux-Viry, M.; Pechev, S.; Saito, N.; Ryoken, H.; Haneda, H.; Sasaki, T.
This contribution consists in a microreview of our research activities for the last three years period concerning the synthesis and characterisation of M@ZnO nanocolloids with M = Ti, Eu, Co and [Mo6Br14]2−. Using, these different 'polymeric' nanocolloids, thanks to the high concentration, we demonstrate the possibility to prepare various functional nanomaterials like gels, nanosized powders or functional thin films (oxynitrides or oxides) with numerous shapes such as plates and fibres. Versatile 'ZnTiON' coloured or Eu, Ti@ZnO red-luminescent thin films are developed.